Construct Validation Of Special Education Teacher Competencies For Inclusive Education: A Confirmatory Analysis Approach - Kusuma, Distiani Fitria (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to validate the construct of special education teacher competencies, which include pedagogical, social, and professional competencies. Data analysis was conducted using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) on 71 special education teachers in East Java. The CFA results showed that the three competency dimensions had good model fit based on the Comparative Fit Index (CFI) and Root Mean Square Error of Approximation (RMSEA) values. Among the three dimensions, professional competency had the highest level of fit, thus best representing the core competencies of special education teachers. In addition, teachers with more than ten years of work experience and special education backgrounds (PLB) demonstrated higher levels of adaptive professional competency. These findings provide empirical evidence regarding the essential competencies of special education teachers and can serve as a basis for developing competency improvement programs that support inclusive education practices.